Preparation of levofloxacin thermo-sensitive gel and clinical application in the treatment of suppurative otitis media. (May 2014) - Li, Cong; Gu, Jian; Mao, Xiaohui; Ao, Huafei; Yang, Xizhi
Abstract Conclusion: The levofloxacin thermo-sensitive gel prepared using 17% poloxamer 407 (P407) can successfully treat suppurative otitis media (SOM) through the well-controlled release of levofloxacin targeted against the inflammation. Objective: To evaluate the preparation method and therapeutic effect of levofloxacin thermo-sensitive gel used in the treatment of SOM. Methods: The phase inversion temperatures of 16%, 17%, 18%, 19%, and 20% P407 or P407 solution with 3 mg/ml levofloxacin were determined and the one close to 34°C was selected as the optimal concentration. Then a model of SOM was induced by injection of 0.1 ml Staphylococcus aureus (1 × 108/L) in the left ear of 32 Sprague Dawley (SD) rats. Normal saline injected in the right ear was used as the control. Then rats were treated with 0.1 ml normal saline (group A), levofloxacin (group B), P407 (group C), and levofloxacin thermo-sensitive gel (group D) (n = 8). The tympanic membranes were evaluated by otoscopy and hematoxylin and eosin (H&E) staining. Results: The optimal concentration of P407 was 17% and the release of levofloxacin in thermo-sensitive gel followed zero-order kinetics. Levofloxacin thermo-sensitive gel and levofloxacin drops could both alleviate the local inflammation in the first 3 days, but levofloxacin drops could not inhibit the recurrence of SOM, while the levofloxacin gel performed continuous drug delivery into inflammation without recurrence.